A concepção de subjetividade na “Fenomenologia da Percepção” - Gomes, Ana Gélica Alves (2021)
Merleau-Ponty, french philosopher, aimed to describe, through phenomenology, the relation between the human being and sensitive world. Through his thesis Phenomenology of Perception, from 1945, he described the perceptive act, treating as an originary phenomenon, through critics to empirism and intellectualism in perception approach. Also in that work studies the lived body sense, concept which aims to overcome the mind x body dichotomy and contradicts the objectivist analysis of human body. This body is described by the philosopher regarding proper attributes that characterizes it while body-subject, as motricity, spaciality, afetivity, sexuality and languages, treated in first part of Phenomenology of Perception: the body. In this way, the body becomes to be perceived as a vehicle in the world, in the existence. The aim of this thesis is to think the human subjectivity as being connected to this bodyness, as determined in the Phenomenology of Perception. In this way, it is discussed, firstly, the merleaupontyan phenomenological thinking regarding perception, which comes from Husserl phenomenology, but also changes it. After, searches to discuss the lived body, as reflexive and intentional instrument of the being in the world, showing, thus, as the root of a body-mediated subjectivity and intentional. Finally, following the Merleau-Ponty thinking in the presented work, it is described deeply the body lived and world lived relation, highlighting, specially, the intersubjectivity and temporality as central concepts to think an embodied subjectivity. It is concluded that the Phenomenology of Perception presents a subjectivity that, despite singular and embodied, can not be seen from an individualist perspective, which dispenses of a shared lived world.